Experimental testing and process parametrization - Rodrigues, Daniela Sofia Sousa (2020)
In this chapter, a characterization to the resulting FDM-printed parts and hybrid manufactured, essentially in terms of mechanical properties, is exposed and discussed. Once evaluated the polymeric thermal and/or mechanical response of the neat filaments, we were able to move forward with the mechanical characterization of the different printed parts developed under different methodologies and distinct purposes. After all this, the performance of hybrid trials in order to evaluate system functionalities, as well as hybridization strategies associated with the presence of AM supports during milling and layer adhesion on the top of a completely cured and machined surface was pursued. Additionally, it was also studied advanced preprocessing methods such as adaptive or curved slicing assessed in the experimental hybrid system with a special attention to the constraints of using long or continuous carbon fibres. All the experimental methodologies carried out and obtained results are described in detail herein.